2020
DOI: 10.1021/acs.jpca.9b09287
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evolution and Stability Trend of Small-Sized Gold Clusters Aun (n = 20–30)

Abstract: Structural evolution and stability pattern of pure neutral gold clusters Au n in the small size range of n = 20–30 are examined using density functional theory (DFT) calculations. The equilibrium geometries are either confirmed or determined, and some new ground state structures are identified. The most stable configurations of Au21–Au23 sizes are formed by adding extra gold atoms to the highly stable pyramidal structure of Au20, while flat-cage shapes are the best candidates for the global minima of both Au2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 62 publications
2
31
0
Order By: Relevance
“…[27,32] Indeed, inclusion of longrange exchange effects in the LC-BLYP functional clearly improves the calculated orbital energies in noble clusters. [30,33] 3 | RESULTS AND DISCUSSION…”
Section: Methodsmentioning
confidence: 99%
“…[27,32] Indeed, inclusion of longrange exchange effects in the LC-BLYP functional clearly improves the calculated orbital energies in noble clusters. [30,33] 3 | RESULTS AND DISCUSSION…”
Section: Methodsmentioning
confidence: 99%
“…Of the latter, both 27a‐4 and 27a‐6 are likely to dominate the higher‐lying population. While the former can be generated by the removal of the uppermost, lowermost, and corner atoms of a regular trigonal bipyramid Au 30 , 34 the latter is formed by the addition of one extra gold atom to the most stable form of Au 26 35 . These forms are found to be around 0.3–0.4 eV higher in energy.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that all the results discussed above are obtained at the TPSS/cc‐pVDZ‐PP level. Previous theoretical studies 34,36 pointed out that the energies of gold clusters are extremely sensitive to the density functional employed. Indeed, as can be seen from Table 1, each functional yields a profoundly different energy landscape.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent DFT calculations [ 91 , 116 , 117 ] revealed that the mechanism of metallic nanoparticle formation, especially of AuNPs and AgNPs, consists of several steps that begin with the formation of agglomerates with M I -M I (M = Ag or Au) bonds and M 0 -M I bonds that are eventually reduced to form Ag n 0 or Au n 0 as the intermediate to AgNPs or AuNPs. Silver and gold atoms are known, respectively, to form Ag–Ag [ 118 , 119 ] and Au–Au [ 75 , 120 , 121 , 122 , 123 , 124 , 125 ] bonds and form clusters. Bond formation is also known to occur between silver atoms and silver ions [ 92 , 119 , 126 , 127 , 128 ], between silver ions [ 129 , 130 , 131 ], and between gold ions [ 80 , 120 , 131 , 132 ].…”
Section: Formation Of M-m M-m I and M I -M I Bondsmentioning
confidence: 99%